2017
DOI: 10.4274/balkanmedj.2016.0133
|View full text |Cite
|
Sign up to set email alerts
|

Fetal Nasal Bone Length as a Novel Marker for Prediction of Adverse Perinatal Outcomes in the First-Trimester of Pregnancy

Abstract: Background:Adverse outcomes of pregnancy are a challenging health-care problem. Prediction of adverse pregnancy outcomes is important to prevent the morbidities of the foetus and the mother.Aims:To study the clinical interest of fetal nasal bone length in predicting adverse pregnancy outcomes in the first trimester of pregnancy.Study Design:A population-based retrospective cohort study.Methods:Data from 868 women with first-trimester fetal nasal bone length and birth records available were enrolled. Fetal nasa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 16 publications
0
3
0
1
Order By: Relevance
“…Absence or hypoplasticity of NB has been considered as one of the strongest ultrasound markers for Down’s syndrome and other chromosomal abnormalities in the first and second trimester in previous studies ( Canda et al, 2017 ; Du Y et al, 2018 ; Bernardeco et al, 2022 ). In our present study, 27.81% (89/230) of fetuses with NBA were found to have chromosomal abnormalities, including 53 cases of trisomy 21, which was the most common type of chromosomal aneuploidy and accounted for 59.55% (53/89) of all abnormalities detected.…”
Section: Discussionmentioning
confidence: 99%
“…Absence or hypoplasticity of NB has been considered as one of the strongest ultrasound markers for Down’s syndrome and other chromosomal abnormalities in the first and second trimester in previous studies ( Canda et al, 2017 ; Du Y et al, 2018 ; Bernardeco et al, 2022 ). In our present study, 27.81% (89/230) of fetuses with NBA were found to have chromosomal abnormalities, including 53 cases of trisomy 21, which was the most common type of chromosomal aneuploidy and accounted for 59.55% (53/89) of all abnormalities detected.…”
Section: Discussionmentioning
confidence: 99%
“…Canda и соавт. определили, что превышение длины носовой кости плода более 95-го перцентиля часто сочетается с ПИОВ (точность данного наблюдения составляет 94 %, p = 0,001), тогда как превышение 99-го перцентиля статистически значимо связано с преждевременными родами и маловодием (точность -95 %, p = 0,006; точность -97 %; p = 0,014 соответственно) [43].…”
Section: инструментальные методы оценки вероятности несвоевременного ...unclassified
“…Several studies have con rmed its close association with fetal chromosomal disorders, particularly trisomy 21 [2,6,7] , as well as adverse pregnancy outcomes and fetal or perinatal death. Recent studies have demonstrated that fetal nasal bone anomalies may serve as objective markers of dysmorphism associated with genomic abnormalities [8][9][10] , including large fragment deletions, duplications, and pathogenic copy number variations (P CNVs). However, the cohort included in the study was not su ciently large, and no grouping analysis was performed to examine the different trimesters when fetal nasal bone anomalies were detected.…”
Section: Introductionmentioning
confidence: 99%